The Biofuel Crops in Global Warming Challenge: Carbon Capture by Corn, Sweet Sorghum and Switchgrass Biomass Grown for Biofuel Production in the USA - Holou, Roland Ahouélété Yaovi; Kindomihou, Valentin Missiakô (My University, 2017)
This research evaluates potential carbon capture of sweet sorghum, switchgrass, and corn grown in Portageville, Missouri, from 2007 to 2009. Our results showed that corn grain C content averaged 43%, whereas C grain captured was 1.3–4.7 Mg C ha −1 depending on year and N rate. N fertilization significantly increased C capture, but not C content of grain. C capture by switchgrass depended on cultivars and harvest date. Switchgrass cv. Alamo biomass contained 46% C compared to 44% C for Blackwell's. Alamo maximum C capture depended on year, being 9.8 Mg C ha −1 in 2008 and 13.4 Mg C ha −1 in 2009. C is equivalent to 32.3–49.6 Mg CO 2  ha −1 , while Blackwell captured 3.7– 4.4 Mg C ha −1 . C in sweet sorghum biomass ranged from 42 to 45%, whereas total C capture ranged from 3.2 to 13.8 Mg ha −1 according to year, soil, and N rate. The highest C capture appeared in loam. Sweet sorghum aboveground biomass showed 82% C captured in the stalk. When converted into CO 2 , C captured by sweet sorghum was equivalent to 12–51 Mg CO 2  ha −1 . In addition to their biofuel potential, corn, switchgrass, and sweet sorghum can substantially contribute to environmental cleaning by capturing a significant amount of CO 2 .
Keywords: carbon; corn; sweet sorghum; switchgrass; global warming; CO 2